A 4-Step Hospital Deployment Strategy for AI in Medical Imaging - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Explore a structured 4-step hospital deployment strategy for AI in medical imaging, covering pilot testing, validation, system integration, and continuous monitoring.
Keywords: AI deployment; medical imaging AI; clinical validation; PACS integration; digital health